Occupational justice and social inclusion among people living with HIV and people with mental illness: a scoping review - Clement Nhunzvi; Lisa Langhaug; Edwin Mavindidze; Roshan Galvaan (BMJ Open)
Objective To explore ways in which occupational justice and social inclusion are conceptualised, defined and operationalised in highly stigmatised and chronic conditions of mental illness and HIV.Design This scoping review protocol followed Arksey and O’Malley’s (2005) Scoping Review Framework.Data sources and eligibility The following databases were searched for the period January 1997 to January 2019: Medline via PubMed, Scopus, Academic Search Premier, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Africa-Wide Information, Humanities International Complete, Web of Science, PsychInfo, SocINDEX and grey literature.Eligible articles were primary studies, reviews or theoretical papers which conceptualised, defined and/or operationalised social inclusion or occupational justice in mental illness or HIV.Study appraisal and synthesis We undertook a three-part article screening process. Screening and data extraction were undertaken independently by two researchers. Arksey’s framework and thematic analysis informed the collation and synthesis of included papers.Results From 3352 records, we reviewed 139 full articles and retained 27 for this scoping review. Definitions of social inclusion and occupational justice in the domains of mental illness and HIV were heterogeneous and lacked definitional clarity. The two concepts were conceptualised as either processes or personal experiences, with key features of community participation, respect for human rights and establishment and maintenance of healthy relationships. Conceptual commonalities between social inclusion and occupational justice were premised on social justice.Conclusions To address lack of clarity, we propose further and concurrent exploration of these concepts, specifically with reference to persons with comorbid mental health disorders such as substance use disorders and HIV living in low-income countries. This should reflect contextual realities influencing community participation, respect for human rights and meaningful occupational participation. From this broadened understanding, quantitative measures should be applied to improve the standardisation of measurements for occupational justice and social inclusion in policy, research and practice.